TIME CONTROL SYSTEM WITH ADDITIONAL FEATURES - KOTELENETS, YULIIA; BONDARENKO, NATALIIA; BONDARENKO, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Time management systems have become an integral element in many areas of human activity, such as transportation, electronics, telecommunications etc. However, creating functional time management systems with additional features is becoming an increasingly important task. For example, modern mobile devices used in various fields require accurate time control systems to ensure the operation of various functions, such as geolocation, photography, and video, as well as to implement other additional functions. A time control system with additional functions based on a quartz resonator has been developed. The system has advanced features that can be used to perform various functions such as displaying data on the screen, processing data from temperature and humidity sensors used to monitor indoor climate conditions. The system uses high quality components such as a crystal with an I2C interface for communication and an LCD display. The device provides accurate time synchronization according to the use of the Wi-Fi module. The system is powered via a USB port and can therefore be easily connected to a computer or laptop. It has a compact size and can be used in a variety of devices that require accurate time tracking. Due to the relatively low cost of components and ease of manufacture, the system can be used to create prototypes and small batches of equipment in various industrial and scientific fields.